Global prevalence of stigmatization and violence against healthcare workers during the COVID‐19 pandemic: a systematic review and meta‐analysis. Issue 6 (12th July 2022) - Saragih, Ita Daryanti; Tarihoran, Dame Elysabeth Tuty Arna Uly; Rasool, Akhtar; Saragih, Ice Septriani; Tzeng, Huey‐Ming; Lin, Chia‐Ju
Abstract: Purpose: During COVID‐19, stigmatization and violence against and between professional healthcare workers worldwide are increasing. Understanding the prevalence of such stigmatization and violence is needed for gaining a complete picture of this issue. Therefore, the purpose of this review was to update estimates of the prevalence of stigmatization and violence against healthcare workers during the pandemic. Design: A systematic review and meta‐analysis was conducted. Methods: This review followed PRISMA guidelines and encompassed these databases: PubMed, Academic Search Complete, CINAHL, Web of Science, MEDLINE Complete, OVID (UpToDate), and Embase (from databases inception to September 15, 2021). We included observational studies and evaluated the quality of the study using the Joanna Briggs Institute methodology. Further, a random effects model was used to synthesis the pooled prevalence of stigmatization and violence in this study. Findings: We identified 14 studies involving 3452 doctors, 5738 nurses, and 2744 allied health workers that reported stigmatization and violence during the pandemic. The pooled prevalence was, for stigmatization, 43% (95% confidence interval [CI]: 21% to 65%) and, for violence, 42% (95% CI: 30% to 54%). Conclusions: Stigmatization and violence during the COVID‐19 pandemic were found to have affected almost half the studied healthcare workers. Healthcare professionals are more prone to be stigmatized by the community and to face workplace violence. Clinical Relevance: Health administrators and policymakers should anticipate and promptly address stigmatization and violence against and between healthcare workers, while controlling the spread of COVID‐19. Health care systems should give serious attention to the mental health of all health providers.